Improving the quality and use of birth, death and cause-of-death information : guidance for a standards-based review of country practices (World Health Organization, 2010)
Sumario: El tema trata sobre la orientación que imparte la OMS para ayudar a los países a evaluar sistemáticamente el funcionamiento de sus sistemas de registro civil y estadísticas.